PENGARUH RETRUN ON ASSET, DAN DEBT EQUITY RATIO TERHADAP TINGKAT UNDERPRICING - Wardana, Nanda Kusuma (Universitas Muhammadiyah Tangerang, 2021)
this study’s purpose is to know the effect of return on asset (ROA), and debt equity ratio (DER) that do underpricing in Initial Public Offering (IPO). This research was a quantitive research, and for the data was use secondary data from Indonesia stock exchange website and company website. Company whom conduct an IPO on Indonesia Stock Exchange in 2015-2019 was the population on this research. The sample use purposive sampling method until get 50 company with the criteria. The method of data analyze used multiple linier regressions with the program IBM SPSS 25. The result of this study used T Test for ROA and DER was -1,133 and -1,138. And F test for sumultaneos had significant value was 0,570. It means Return on asset (ROA) and Debt equity ratio (DER) had not effect on underpricing even partial or simultaneous.